2012
DOI: 10.1603/me11260
|View full text |Cite
|
Sign up to set email alerts
|

Host Preference of the Arbovirus VectorCulex erraticus(Diptera: Culicidae) at Sonso Lake, Cauca Valley Department, Colombia

Abstract: Culex erraticus (Dyar & Knab) is a competent vector of Eastern equine encephalitis virus and subtype IC Venezuelan equine encephalitis virus, and both St. Louis encephalitis virus and West Nile virus have been isolated from field-collected specimens. Previous bloodmeal analysis studies have shown this species to be a generalist, feeding on a variety of mammals, birds, reptiles, and amphibians. This behavior can bridge arboviral transmission across different vertebrate groups. Our study examined the host prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Finally, an evaluation of host availability in order to estimate mosquito host preferences in field conditions was conducted in 11 studies (Table S3 ). Ten of them quantified host availability at mosquito capture sites, by one or a combination of the following tools: census of individuals providing absolute counts (e.g., Gomes et al 2003 ; Bataille et al 2012 ), visual, and/or auditory sampling of avian species (e.g., Mendenhall et al 2012 ; Hoyos Loaiza 2018 ), surveys to residents (e.g., Rubio-Palis et al 1994 ), and bibliographic sources or data bases available for the area (e.g., Alencar et al 2005 ). The obtained information was used considering the raw number of individuals (in the majority of the studies) or standardized by animal weight (e.g., Lardeux et al 2007 ; Saavedra et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, an evaluation of host availability in order to estimate mosquito host preferences in field conditions was conducted in 11 studies (Table S3 ). Ten of them quantified host availability at mosquito capture sites, by one or a combination of the following tools: census of individuals providing absolute counts (e.g., Gomes et al 2003 ; Bataille et al 2012 ), visual, and/or auditory sampling of avian species (e.g., Mendenhall et al 2012 ; Hoyos Loaiza 2018 ), surveys to residents (e.g., Rubio-Palis et al 1994 ), and bibliographic sources or data bases available for the area (e.g., Alencar et al 2005 ). The obtained information was used considering the raw number of individuals (in the majority of the studies) or standardized by animal weight (e.g., Lardeux et al 2007 ; Saavedra et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…This mosquito was the only shared species studied by both Hamer et al (2009) and Estep et al (2011), and so the data in these two studies could not be analyzed jointly. Mendenhall et al (2012) For each bird and mosquito species, these authors reported a FR calculated as the ratio between the fraction of mosquitoes that had fed on a given bird species and the fraction of the censused individuals belonging to that bird species in the study area.…”
Section: Data Collectionmentioning
confidence: 99%
“…Primarily a bird-feeding species that transitions to mammals later in the season, Cx. erraticus has been documented with natural infections of eastern equine encephalitis (EEE) virus and WNV (Harrison et al 2009, Mendenhall et al 2012, Mukherjee et al 2012, Godsey et al 2013, Bingham et al 2016. Culex erraticus is a potential bridge vector (Cupp et al 2003(Cupp et al , 2004Cohen et al 2009;Lindsey et al 2018) reported nonhuman cases of EEE in 4 counties and at least 1 human case along the Arkansas-Oklahoma border.…”
Section: Discussionmentioning
confidence: 99%